Establishing the standard method of cochlear implant in Rongchang pig. (4th May 2017) - Chen, Wei; Yi, Haijin; Zhang, Liang; Ji, Fei; Yuan, Shuolong; Zhang, Yue; Ren, Lili; Li, Jianan; Chen, Lei; Guo, Weiwei; Yang, Shiming
Abstract: Conclusions: In this investigation, a large mammal, Rongchang pigs were used to successfully establish a research platform for cochlear implant study on the routine use of it in clinic. Objective: The aim of this study was to establish a standard method of cochlear implant in a large mammal—pig. Methods: Rongchang pigs were selected, then divided into two groups: normal-hearing group (Mitf +/+) and mutation group with hearing loss (Mitf −/−). Cochlear implants were used and ABR and EABR were recorded. The implanted electrodes were observed by X-ray and HE stains. Results: The success with cochlear implant and the best electrode position could be defined in all animals, the coiling of the cochlea reached 1.5–1.75 turns. Immediately after the operation of cochlear implants, the ABR threshold of the operated ear (right) could not be derived for each frequency at 120 dB SPL. Moreover, 7 days after surgery, the low-frequency ABR threshold of the operated ear (right) could be derived partly at 100 dB SPL, but the high-frequency ABR threshold could not be derived at 120 dB SPL. Immediately or 1 week after cochlear implants, the EABR threshold was 90 CL in the Mitf +/+ group. This was obviously lower than the 190 CL in the Mitf −/− group.